A bio-electron microscope using DLC film which living cells can be observed in the atmosphere. (1st January 2013) - Kozuki, T.; Nawachi, N.; Itoh, K.; Kotera, M.; Suga, H.
We studied the high-resolution imaging of a new bio-electron microscope that uses a DLC film as a bulkhead to separate the electron beam source and the sample room. The electron beam source can be setup in a vacuum container, thus placing the sample being observed through the microscope under atmospheric pressure. In order to observe the sample, a thin film penetrable by electrons is required as the bulkhead. In addition, it needs to be strong enough to endure the atmospheric pressure, and the material must be medically safe. This investigation has shown that DLC film is the best film for this purpose, given the influence that the distance of the atmospheric layer has on image acquisition. Moreover, although the acceleration voltage of the present system is 30 kV, it is advised that observations are made at the lowest acceleration possible.